Do Malay estate-distribution practices contribute to lower land values? - Khalid, Haniza (IDOSI Publications, 2014)
The paper describes how complex co-ownership issues arising from estate-distribution can lead to uneconomic farm sizes or sometimes prevent farming activities altogether (through land-use conversion or land abandonment). Muslims in Malaysia rely almost exclusively on Fara’id laws in which ownership of all the deceased’s assets, including land, are apportioned to his beneficiaries. The interaction between the religiously-prescribed estate-distribution methods and the British-introduced land administration system may have indirectly contributed to undervaluation and fragmentation of rural land, mostly owned by Malay households. In the short run, the adverse effects can be seen in the uneconomic farm sizes and eventual conversion of farmland to other uses. In the long run, the trends may erode food production capabilities of the country as well as the Malay-Muslim total land holdings and therefore their economic wealth. Empirical evidence showed that paddy and vacant land, two types of land typically associated with Malays in Malaysia, are indeed valued lower than like-to-like land parcels in other categories. It is hoped that the paper can trigger more in-depth research to better public awareness and inform policy-improvement measures by the present land-related agencies and Muslim affairs authorities.